1997
DOI: 10.1007/bf02945067
|View full text |Cite
|
Sign up to set email alerts
|

Sterigmatocystin — incidence, fate and production byA versicolor in ras cheese

Abstract: Sterigmatocystin (STG) is a toxic metabolite produced by severalAspergillus species. Because of its toxic and carcinogenic properties the occurrence of STG in food is considered to represent a potential hazard to man. The present study was designed to investigate following points: 1 A survey of STG incidence in Ras cheese on local markets. Ras cheese samples were collected from Cairo, Giza and Kalubia governorates. Thirty five percent of the samples contained the toxin with a mean value of 22.23 μg /kg 2 Fate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…It was shown that the disappearance of STC from contaminated milk depends on the type of starter culture, the storage period and the type of milk. The same group showed also that during cheese processing, 80 % of the toxin present in milk was found in the curd and only 20 % was found in the whey, related to low solubility in aqueous media, according to the authors (Abd Alla et al, 1996;Metwally et al, 1997).…”
Section: Food Processingmentioning
confidence: 93%
See 1 more Smart Citation
“…It was shown that the disappearance of STC from contaminated milk depends on the type of starter culture, the storage period and the type of milk. The same group showed also that during cheese processing, 80 % of the toxin present in milk was found in the curd and only 20 % was found in the whey, related to low solubility in aqueous media, according to the authors (Abd Alla et al, 1996;Metwally et al, 1997).…”
Section: Food Processingmentioning
confidence: 93%
“…The toxin was not found in the inner part of the same positive samples. STC was detected also in the outer layer (1-2 cm) of mouldy cheese with concentrations up to 9000 µg/kg in the Netherlands (Northolt et al, 1980;Northolt and van Egmond, 1982) and in Egypt, where 100 samples of hard cheese were analysed using TLC (Abd Alla et al, 1996;Metwally et al, 1997). From the 100 samples, 35 samples contained STC with a mean value of 24 µg/kg and a range between 10 and 63 µg/kg.…”
Section: Cheesementioning
confidence: 99%
“…STC je detektovan u žitima, hlebu, siru, začinima, kafi, pasulju, soji, pistaćima, koštičavom voću, pivu, povrću, stočnoj hrani i silaži [45,46,56,72].…”
Section: Sterigmatocistin (Stc) Je Sekundarni Metabolit Nekih Vrsta Iunclassified
“…Food processing (e.g., roasting, fermentation, bread and cheese making, milling, heating, or enzymes) can potentially lead to alterations in the levels of STG; the extent of these modifications depends on the type of food involved and the food processing conditions [14,15]. The migration, transformation and degradation of contaminants in food processing, such as mycotoxins, is closely related to its physicochemical properties, especially the melting point, the Octanol-Water Partition Coefficient (Kow), water solubility, and vapor pressure [16][17][18]. STG has a high melting point (246 • C) and is relatively insoluble in water (1.44 mg/L at 25 • C); these characteristics make it stable in the food and surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Veršilovskis et al [18] reported that STG remained stable during the breadmaking process; the levels of STG were determined in 5 of the 29 bread samples analyzed at concentrations ranging from 2.4 to 7.1 µg/kg in Riga, Latvia. Metwally et al [17] reported high levels of STG (80%) in the curd and much lower levels (20%) in the whey during the cheese making process, thus demonstrating the low solubility of STG in aqueous media.…”
Section: Introductionmentioning
confidence: 99%